Case report: a rare case of ocular leptospirosis - I Made Surya Dinajaya; Ida Ayu Ary Pramita; I Gusti Ayu Made Juliari; Ni Ketut Niti Susila; I Made Agus Kusumadjaja (DiscoverSys Inc., 2022)
Background: Ocular leptospirosis is a rare condition. Transmission of leptospirosis is caused by the bacterium leptospira interrogans transmitted directly or indirectly from animals to humans (zoonosis). Ocular manifestations often caused by leptospirosis are conjunctivitis, keratitis, uveitis (anterior, intermediate, posterior, and panuveitis), complicated cataracts, choroiditis, papillitis, and macular edema. Uveitis is a latent manifestation of leptospirosis. Proper management can lead to a good prognosis of visual.Case Presentation: Male patient, 55 years old, with complaints of both red and blurry eyes since 5 days. Blurring comes slowly with pain, glare, and seeing shadows like spider webs. The patient's previous medical history was hospitalized because of Weil's disease. Examination of the anterior segment of both eyes revealed eyelid spasm, conjunctival injection, corneal infiltrate, keratic precipitate, and posterior synechiae on both eyes. While in the posterior segment found cells 4+ in the vitreous. The patient was treated with antibiotics and topical steroids, and visual acuity was improved.Conclusion: Leptospirosis uveitis can have various presentations during the acute and chronic phases of the disease. Even when ocular involvement is extensive and severe, most patients have a good visual prognosis with appropriate therapy. Timely diagnosis is essential to maximize the potential for visual acuity improvement and appropriate systemic monitoring and treatment of extraocular involvement in this potentially fatal condition. Good sanitation in the community plays an important role in preventing exposure to leptospirosis.